This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: roberts (eer474) HW 11 windle (56747) 1 This printout should have 5 questions. Multiplechoice questions may continue on the next column or page find all choices before answering. 001 (part 1 of 2) 10.0 points Use the graphs of f and g to evaluate the functions. y 1 2 3 4 1 2 3 4 x y = f ( x ) y 1 2 3 4 1 2 3 4 x y = g ( x ) a) ( f g )(1). Correct answer: 1. Explanation: ( f g )(1) = f (1) g (1) = 2 3 = 1 002 (part 2 of 2) 10.0 points b) ( fg )(4). Correct answer: 0. Explanation: ( fg )(4) = f (4) g (4) = 4 = 0 003 10.0 points Simplify as much as possible the expression for the function h = 2 f g when f ( x ) = x 2 + 3 x + 2 , g ( x ) = x 2 x 2 . 1. h ( x ) = 3 x 2 + 7 x + 2 2. h ( x ) = x 2 + 7 x + 2 3. h ( x ) = 3 x 2 + 5 x + 2 4. h ( x ) = x 2 + 5 x + 6 5. h ( x ) = x 2 + 7 x + 6 correct 6. h ( x ) = 3 x 2 + 5 x + 6 Explanation: The sum h = 2 f g of functions f and g is given by h ( x ) = 2 f ( x ) g ( x ) = 2( x 2 + 3 x + 2) ( x 2 x 2) ....
View
Full
Document
This note was uploaded on 11/08/2010 for the course M 305G taught by Professor Léger during the Fall '08 term at University of Texas at Austin.
 Fall '08
 Léger
 Math

Click to edit the document details